Assessment of ventilatory neuromuscular drive in patients with obstructive sleep apnea - Bittencourt,L.R.A. (1998)
The presence of abnormalities of the respiratory center in obstructive sleep apnea (OSA) patients and their correlation with polysomnographic data are still a matter of controversy. Moderately obese, sleep-deprived OSA patients presenting daytime hypersomnolence, with normocapnia and no clinical or spirometric evidence of pulmonary disease, were selected. We assessed the ventilatory control and correlated it with polysomnographic data. Ventilatory neuromuscular drive was evaluated in these patients by measuring the ventilatory response (VE), the inspiratory occlusion pressure (P.1) and the ventilatory pattern (VT/TI, TI/TTOT) at rest and during submaximal exercise, breathing room air. These analyses were also performed after inhalation of a hypercapnic mixture of CO2 (DP.1/DPETCO2, DVE/DPETCO2). Average rest and exercise ventilatory response (VE: 12.2 and 32.6 l/min, respectively), inspiratory occlusion pressure (P.1: 1.5 and 4.7 cmH2O, respectively), and ventilatory pattern (VT/TI: 0.42 and 1.09 l/s; TI/TTOT: 0.47 and 0.46 l/s, respectively) were within the normal range. In response to hypercapnia, the values of ventilatory response (DVE/DPETCO2: 1.51 l min-1 mmHg-1) and inspiratory occlusion pressure (DP.1/DPETCO2: 0.22 cmH2O) were normal or slightly reduced in the normocapnic OSA patients. No association or correlation between ventilatory neuromuscular drive and ventilatory pattern, hypersomnolence score and polysomnographic data was found; however a significant positive correlation was observed between P.1 and weight. Our results indicate the existence of a group of normocapnic OSA patients who have a normal awake neuromuscular ventilatory drive at rest or during exercise that is partially influenced by obesity